Earning Quality Effect on Stock Returns: GCG and CSR Mechanism - Permata Sari, Diah; Setiyawati, Hari (University of Merdeka Malang, 2021)
This study explores the effect of corporate governance mechanisms and disclosure of corporate social responsibility on earnings quality and the effect on stock returns. The mining sector research analysis is indexed on the Indonesia Stock Exchange for the period 2014 to 2018. The research method used is causal research, with the analysis method used is multiple linear regression. The sampling technique used purposive sampling. The results showed that Managerial Ownership, Institutional Ownership, Independent Commissioners, and CSR disclosure did not affect earnings quality, while the Audit Committee and Stock Returns significantly affected earnings quality. This study's findings contribute to financial performance, particularly the relationship between corporate governance, CSR disclosure, and earnings quality. These findings can be a consideration for investors in making policies on their investments. DOI : https://doi.org/10.26905/jkdp.v25i2.5528